Scopes, Options, and Horizons – Key Issues in Decision Structuring - Hansson, Sven Ove (Ethical Theory and Moral Practice, 2018)
Real-life decision-making often begins with a disorderly decision problem that has to be clarified and systematized before a decision can be made. This is the process of decision structuring that has largely been ignored both in decision theory and applied decision analysis. In this contribution, ten major components of decision structuring are identified, namely the determination of its scope (the issues to be covered by the decision), subdivision (if and in that case how the decision will divided into separate parts), agency (who will make the decision), timing, options, control ascriptions, framing, horizon (the consequences and other aspects of outcomes that will be taken into account), criteria (of success) and (provisions for) restructuring. Four of these components, namely the scope, subdivision, options, and horizon of a decision, are subjected to a more detailed analysis.